Evaluation of International Shipping Alliance: A Case Study of Transport Capacity and Cost Efficiency Influence the Quality of Cooperation Inter-Country Using Discriminant Analysis - Natalia, Tia; Muhammad, Fadel; Achmadi, Tri (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
Shipping is a source of income that entrepreneurs increasingly demand because of the public's high use of this service, both for traveling and sending and transporting goods. Shipping companies offer their services domestically and cooperate with foreign shipping companies to increase revenue. In addition to increasing revenue, this business can increase the quality of cooperation between countries, which can be seen from transportation capacity and cost efficiency because more fleets will be provided, and infrastructure will be adequate because it consists of more than one country. Even though the shipping system cooperates with other countries and has an international standard, this does not necessarily satisfy the public with the service in the form of transportation capacity and fees charged. Not infrequently, many people complain that the costs incurred are quite high, but the implemented system is not following what most people expect. To see the quality of cooperation between countries (Y), this research will look at the transportation capacity factor (X1) and also cost efficiency (X2) using the discriminant analysis method. Discriminant analysis is a statistical method used to categorize an object into two or more groups based on the independent variable (X) used. The results obtained in this study show that the majority of people are satisfied with the existence of an international shipping alliance that is equal to 78%, with only cost efficiency (X2) being the main factor affecting customer satisfaction with the resulting classification accuracy rate of 71% and good models by 61%.